1979
DOI: 10.1136/jnnp.42.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged azathioprine treatment of non-remitting multiple sclerosis

Abstract: SUMMARY Two groups of 85 and 42 ambulatory patients with moderately advanced nonremitting multiple sclerosis were treated for six to 14 and three to six years with daily azathioprine. Less than 10% of these patients became confined to a wheelchair. This far exceeds any possible result in a group of non-remitting multiple sclerosis patients not so treated.There has been convincing evidence for at least a partial role of immune mechanisms in the production of multiple sclerosis for many years. These data still s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Merfin's [6] arid Zeeberg's [15] studies may explain the lack of difference between treated and control cases reported in their papers. However, in agreement with Rosen's [10] impressive results (9% of the treated vs 65% of the controls deteriorated after 4.5 years of therapy), we did notice a decreasing trend of the PR in our progressive immunosuppressed patients. However, in agreement with Rosen's [10] impressive results (9% of the treated vs 65% of the controls deteriorated after 4.5 years of therapy), we did notice a decreasing trend of the PR in our progressive immunosuppressed patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Merfin's [6] arid Zeeberg's [15] studies may explain the lack of difference between treated and control cases reported in their papers. However, in agreement with Rosen's [10] impressive results (9% of the treated vs 65% of the controls deteriorated after 4.5 years of therapy), we did notice a decreasing trend of the PR in our progressive immunosuppressed patients. However, in agreement with Rosen's [10] impressive results (9% of the treated vs 65% of the controls deteriorated after 4.5 years of therapy), we did notice a decreasing trend of the PR in our progressive immunosuppressed patients.…”
Section: Discussionsupporting
confidence: 92%
“…Empirical results drawn from other studies are not conclusive for clinical efficacy of this drug in MS, mainly because only 2 previous studies have been performed with controlled double-blind methodology [15,6]. This result would be consistent with the data of Rosen [10], Ellison [3] and Patzold [9], although the last named finds a therapeutic efficacy since the trLrst year of therapy, and only in relapsingprogressive cases. This result would be consistent with the data of Rosen [10], Ellison [3] and Patzold [9], although the last named finds a therapeutic efficacy since the trLrst year of therapy, and only in relapsingprogressive cases.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Adequate immuno-suppression is still difficult to achieve without side effects and longer follow-up studies are required. The results of one such study with Azothiaprine (Rosen, 1979) are encouraging. Two groups of ambulatory patients with moderately advanced non-remitting MS were treated for 6-14 and 3-6 years with Azothiaprine and less than 10% of these patients became confined to a wheelchair over the period of the study which was considerably fewer than would have been expected from the natural history of the disease.…”
Section: Treatmentmentioning
confidence: 95%